After the Crash: the conservation-planning assemblage in an era of austerity. Issue 4 (2nd April 2020) - Pendlebury, John; Scott, Mark; Veldpaus, Loes; van der Toorn Vrijthoff, Wout; Redmond, Declan
ABSTRACT: This paper focuses upon the practice of conservation applied through the planning systems of three European countries, Ireland, the Netherlands and England, here termed conservation-planning. The values and validated practice of conservation-planning are considered in terms of the concept of Authorised Heritage Discourses (AHDs) that are internationally-shaped but nationally articulated in each country, and by a distinct conservation-planning social entity that may be described as an 'assemblage'. The post-2008 period has seen over-arching economic similarities in economic and political forces affecting conservation-planning practice in each country. In each case public-sector austerity measures have been accompanied by ideological re-positionings over the role of the state and a greater emphasis upon 'selling the historic city' has been accompanied by a declining public-sector capacity to manage change within the frame of traditionally established AHDs. The partial withdrawal of the state has in each case resulted in adjustments in the construction of the assemblage and thus in the 'ownership' of the AHDs with a greater involvement of the private sector in these processes. Despite similarities in conservation discourse, shaped by an international AHD, differences exist between the countries considered, which we can better understand by reference to the conservation-planning assemblage in each country.